Analysis of solid uranium particulates on cotton swipes with an automated microextraction-ICP-MS system. Issue 44 (1st November 2022) - Bradley, Veronica C.; Spano, Tyler L.; Thompson, Cyril V.; Ticknor, Brian W.; Dunlap, Daniel R.; Metzger, Shalina C.; Hexel, Cole R.; Manard, Benjamin T.
Abstract : An automated microextraction method coupled to an inductively coupled plasma – mass spectrometer (ICP-MS) was developed for the direct analysis of solid uranium particulates on the surface of cotton swipes. Abstract : An automated microextraction method coupled to an inductively coupled plasma – mass spectrometer (ICP-MS) was developed for the direct analysis of solid uranium particulates on the surface of cotton swipes. The microextraction probe extracts particulates from the sample surface, in a flowing solvent, and directs the removed analyte to an ICP-MS for isotopic determination. The automated system utilizes a mechanical XY stage that is software controlled with the capability of saving and returning to specific locations and a camera focused to the swipe surface for optimal viewing of the extracted locations ( i.e., material present). Here, particulates ( n = 135) were extracted and measured by ICP-MS, including 35 depleted uranyl nitrate hexahydrate (UN) (used for mass bias corrections), 50 uranyl fluoride (UO2 F2 ), and 50 uranyl acetate (UAc) particulates. Blank extractions were performed on the cotton swipes between triplicate sample analyses. Between each swipe extraction, the probe was sent between two wells containing 10% and 5% HNO3 to clean the probe head and to eliminate any analyte carryover between particulates. The measured 235 U/ 238 U and 234 U/ 238 U isotope ratios for the UO2 F2 particulates were 0.00725(8) and 0.000054(4), a percent relative difference (% RD) of −0.041% and −1.7% from the reference isotope ratios determined in-lab through multi-collector ICP-MS analysis of dissolved aliquots of the U material. The UAc samples had a measured 235 U/ 238 U isotope ratio of 0.00206(7), a −0.96% relative difference from the reference value of 0.00208(1). The 234 U/ 238 U and 236 U/ 238 U isotope ratios were 0.000008(1) and 0.000031(4), −5.1% RD and −4.3% RD, respectively. The automated sample stage enabled seamless and rapid particle analysis, leading to a significant increase in throughput versus what was previously possible. Additionally, the saved location capability reduced user sampling error as sampling locations were easily stored and recalled. Analysis of U particles on the swipe surface – including blanks, mass bias, and triplicate extractions – was completed in less than an hour without any sample preparation necessary.